THE QUESTIONS ABOUT SPIRITUAL CULTURE OF XIX CENTURY (ABAI KUNANBAYEV AND SWAMI VIVEKANDA) - Yskakova, Z (Journal of Oriental Studies, 2016)
This article was prepared within the project "Spiritual Attunement Kazakh and Indian thinkers." It is the first attempt to review the heyday of the world of spiritual culture in the XIX century through the prism of the life and work of Abay and Swami Vivekananda - two historical figures, two geniuses, representatives of two different nations: Kazakh and Indian, in the artistic heritage of which we find a reflection of the universal ideas humanity and lofty spirituality.